2014
DOI: 10.4236/gep.2014.22023
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Dibutyl Phthalate (DBP) and Benzo(a)Pyrene on Fertility in Male Rats

Abstract: Our previous studies revealed the polycyclic aromatic hydrocarbon and phthalic acid esters were the major organic pollutants in the Jialing River and Yangtze River in the Three Gorges area, and they might cause the toxicity in male fertility when combined. Thus we used di-n-butyl phthalate (DBP) and Benzo(a)pyrene (Bap) as their representatives respectively to explore their effects on the spermatogenesis in male rats. Male Sprague Dawley rats were randomly divided into 4 groups and respectively exposed to corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…While in coiled tail, co-administration with ginger alone produced better effects than co-administration with Se alone or coadministration with both ginger and Se. The findings of the current study could be explained by Huang et al [27] and Alam & Hoque [9] who reported that, DBP has adverse effects on the reproductive system of male, including disturbing the secretion of testosterone, influencing the production and morphology of sperm and damaging the seminiferous tubule, which may induce through oxidative stress from their ROSmetabolites. Di-butyl phthalate causes atrophy in the seminiferous tubules, decreases SOD and GSH-Px activities and increase catalase activity, which indicates an oxidative stress state in the testis.…”
Section: Discussionsupporting
confidence: 53%
“…While in coiled tail, co-administration with ginger alone produced better effects than co-administration with Se alone or coadministration with both ginger and Se. The findings of the current study could be explained by Huang et al [27] and Alam & Hoque [9] who reported that, DBP has adverse effects on the reproductive system of male, including disturbing the secretion of testosterone, influencing the production and morphology of sperm and damaging the seminiferous tubule, which may induce through oxidative stress from their ROSmetabolites. Di-butyl phthalate causes atrophy in the seminiferous tubules, decreases SOD and GSH-Px activities and increase catalase activity, which indicates an oxidative stress state in the testis.…”
Section: Discussionsupporting
confidence: 53%
“…Huang et al reported that the toxicity of BaP was more than dibutyl phthalate for male rats' fecundity (Huang et al 2014). Therefore, the toxicity of the metabolite (dibutyl phthalate) of PAHs in the degradation process should be lower than PAHs, which illustrated that biodegradation of PAHs could decrease the toxicity of PAHs.…”
Section: Analysis Of Pahs Metabolitesmentioning
confidence: 99%